The involvement of Elf5 in regulating keratinocyte proliferation and differentiation processes in skin. - Anhua Hu; Maximilian E Pickup; Maryam A Lawal; Hetal J Patel; Mohammed I Ahmed (PLoS ONE)
Skin and hair development is regulated by multitude of programs of activation and silencing of gene expression to maintain normal skin and hair follicle (HF) development, homeostasis, and cycling. Here, we have identified E74-like factor 5 (Elf5) transcription factor, as a novel regulator of keratinocyte proliferation and differentiation processes in skin. Expression analysis has revealed that Elf5 expression was localised and elevated in stem/progenitor cell populations of both the epidermis (basal and suprabasal) and in HF bulge and hair germ stem cell (SCs) compartments during skin and hair development and cycling. Expressional and functional analysis using RT-qPCR, western blot and colony forming assays, revealed that Elf5 plays an important role in regulating keratinocyte proliferation and differentiation processes as well as potentially determining cell fate by regulating the stem/progenitor cell populations in skin and HFs. These data will provide a platform for pharmacological manipulation of Elf5 in skin, leading to advancements in many areas of research, including stem cell, regenerative medicine, and ageing.